The role of mosquitoes in the diet of adult dragon and damselflies (odonata) - Pfitzner, Wolf Peter; Beck, Matthias; Weitzel, Thomas; Becker, Norbert (Journal of the American Mosquito Control Association, 2015)
The flood plains of the Upper Rhine Valley provide excellent conditions for the proliferation of mosquitoes as well as for the development of dragon and damselflies. It could be assumed that mosquitoes belong to the diet of the Odonata and that the latter could be harmed by the reduction of the mosquito population with the purpose of diminishing the massive nuisance for the people living there. A total of 41 adult dragonflies and damselflies were examined by immunoblot for remnants of mosquitoes in their guts. A rabbit antiserum against Aedes vexans proteins was used for the immunoblot. Only 3 Aeshna cyanea and 1 Platycnemis pennipes could be shown to have fed on mosquitoes. In specimens of the genus Sympetrum no mosquitoes were detected. It seems very doubtful that mosquitoes are an essential part of the Odonata diet.